Selected global flood preparation and response lessons: implications for more resilient Chinese Cities - F. K. S. Chan; Zilin Wang; Jiannan Chen; Xiaohui Lu; Taiseer Nafea; Burrell Montz; Olalekan Adekola; Alessandro Pezzoli; James Griffiths; Yi Peng; Pengfei Li; Juanle Wang (Natural Hazards, 2023)

Phosphonate cycling supports methane and ethylene supersaturation in the phosphate‐depleted western North Atlantic Ocean - Oscar A. Sosa; Timothy J. Burrell; Samuel T. Wilson; Rhea K. Foreman; David M. Karl; Daniel J. Repeta (Limnology and Oceanography, 2020)
In oligotrophic ocean regions, dissolved organic phosphorus (DOP) plays a prominent role as a source of phosphorus (P) to microorganisms. An important bioavailable component of DOP is phosphonates, organophosphorus compounds with a carbon‐phosphorus (C‐P) bond, which are ubiquitous in high molecular weight dissolved organic matter (HMWDOM). In addition to being a source of P, the degradation of phosphonates by the bacterial C‐P lyase enzymatic pathway causes the release of trace hydrocarbon gases relevant to climate and atmospheric chemistry. In this study, we investigated the roles of phosphate and phosphonate cycling in the production of methane (CH 4 ) and ethylene (C 2 H 4 ) in the western North Atlantic Ocean, a region that features a transition in phosphate concentrations from coastal to open ocean waters. We observed an inverse relationship between phosphate and the saturation state of CH 4 and C 2 H 4 in the water column, and between phosphate and the relative abundance of the C‐P lyase marker gene phnJ . In phosphate‐depleted waters, methylphosphonate and 2‐hydroxyethylphosphonate, the C‐P lyase substrates that yield CH 4 and C 2 H 4 , respectively, were readily degraded in proportions consistent with their abundance and bioavailability in HMWDOM and with the concentrations of CH 4 and C 2 H 4 in the water column. We conclude that phosphonate degradation through the C‐P lyase pathway is an important source and a common production pathway of CH 4 and C 2 H 4 in the phosphate‐depleted surface waters of the western North Atlantic Ocean and that phosphate concentration can be an important control on the saturation state of these gases in the upper ocean.

Erratum for “Fluctuating Asymmetry and Growth as Biomarkers for Exposure to Androgen Disrupting Chemicals in Japanese Quail” [10.1007/s10646-005-0013-9(10646-2005-13 Quinn)] - Michael J. Quinn; C. L. Summitt; K. Burrell; M. A. Ottinger (Ecotoxicology, 2005)

Fluctuating Asymmetry and Growth as Biomarkers for Exposure to Androgen Disrupting Chemicals in Japanese Quail - MICHAEL J. C.L. SUMMITT; K. BURRELL; M.A. OTTINGER (Ecotoxicology, 2005)

Effect of deletion and the site of insertion in double copy anti-tat retroviral vectors: viral titres and production of anti-tat mRNA - J. M. Carr; J. K. Calvert; R. Kumar; C. J. Burrell; P. Li (Archives of Virology, 2001)

Analysis of multiple copies of geminiviral DNA in the genome of four closely related Nicotiana species suggest a unique integration event - Mark K. Ashby; Andrew Warry; Eduardo R. Bejarano*; Alaa Khashoggi; Michael Burrell; Conrad P. Lichtenstein* (Plant Molecular Biology, 1997)